Perancangan dan Implementasi Sistem Informasi Persediaan Terintegrasi pada Toko Pakaian Syar’i di Yogyakarta - Moh. Abdul Kholik; Hendri Noviyanto; Arma Fauzi (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This research aims to design and build a web-based syar'i clothing inventory information system at Umama Gallery Yogyakarta. The background of this research is based on the problem of inventory management which has been done manually, which often causes obstacles such as delays in stock information, potential recording errors, wasted paper, and difficulties in preparing inventory reports quickly and accurately. To overcome these problems, a web-based information system was developed by referring to the Software Development Life Cycle (SDLC) Waterfall model, which includes the stages of planning, needs analysis, design, implementation, and testing. Research data was obtained through interviews with store managers and literature studies to support the analysis and design of the system. The implementation results show that the inventory information system built is able to simplify the process of recording and monitoring inventory in real-time, thereby helping to reduce the potential for recording errors and speeding up the reporting process. In addition, this system also reduces dependence on physical documents, making it more environmentally friendly and efficient in the use of resources. Available features include data management of goods, suppliers, users, incoming and outgoing goods transactions, and user account management. The integration of these features supports comprehensive inventory management, improves operational efficiency, and facilitates management in making accurate, data-driven decisions. With this system, Umama Gallery Yogyakarta has gained an effective, reliable, and integrated tool to support smooth operations and more modern and professional inventory management. Similar systems have the potential to be implemented in similar businesses to improve inventory management quality and competitiveness in the digital age.